International Power Trade : The Nordic Power Pool - Carlsson, Lennart (World Bank, Washington, DC, 2012)
Scandinavia, where countries have traded power for decades, has the world's most developed international market for electricity. Recently the trading system has changed dramatically, moving from the old model of cooperation among the leading vertically integrated utilities in each country, under the Nordel agreement, to competitive market rules. Norway and Sweden established a common power market, Nord Pool, in 1996, and Finland joined in June 1998. This Note examines why Nord Pool came into being, what conditions facilitated its development, and what lessons it provides for World Bank client countries.